Large-Scale Alternative Polyadenylation-Wide Association Studies to Identify Putative Cancer Susceptibility Genes - Guo, Xingyi; Ping, Jie; Yang, Yaohua; Su, Xinwan; Shu, Xiao-Ou; Wen, Wanqing; Chen, Zhishan; Zhang, Yunjing; Tao, Ran; Jia, Guochong; He, Jingni; Cai, Qiuyin; et al. (Cancer research, 2024)
Alternative polyadenylation (APA) modulates mRNA processing in the 3'-untranslated regions (3' UTR), affecting mRNA stability and translation efficiency. Research into genetically regulated APA has the potential to provide insights into cancer risk. In this study, we conducted large APA-wide association studies to investigate associations between APA levels and cancer risk. Genetic models were built to predict APA levels in multiple tissues using genotype and RNA sequencing data from 1,337 samples from the Genotype-Tissue Expression project. Associations of genetically predicted APA levels with cancer risk were assessed by applying the prediction models to data from large genome-wide association studies of six common cancers among European ancestry populations: breast, ovarian, prostate, colorectal, lung, and pancreatic cancers. A total of 58 risk genes (corresponding to 76 APA sites) were associated with at least one type of cancer, including 25 genes previously not linked to cancer susceptibility. Of the identified risk APAs, 97.4% and 26.3% were supported by 3'-UTR APA quantitative trait loci and colocalization analyses, respectively. Luciferase reporter assays for four selected putative regulatory 3'-UTR variants demonstrated that the risk alleles of 3'-UTR variants, rs324015 (STAT6), rs2280503 (DIP2B), rs1128450 (FBXO38), and rs145220637 (LDHA), significantly increased the posttranscriptional activities of their target genes compared with reference alleles. Furthermore, knockdown of the target genes confirmed their ability to promote proliferation and migration. Overall, this study provides insights into the role of APA in the genetic susceptibility to common cancers. Significance: Systematic evaluation of associations of alternative polyadenylation with cancer risk reveals 58 putative susceptibility genes, highlighting the contribution of genetically regulated alternative polyadenylation of 3'UTRs to genetic susceptibility to cancer.
Keywords: celogenomová asociační studie; Polymorphism, Single Nucleotide; regulace genové exprese u nádorů; Humans; messenger RNA; Polyadenylation; jednonukleotidový polymorfismus; 3' nepřekládaná oblast; 3' Untranslated Regions; Female; lidé; Quantitative Trait Loci; RNA, Messenger; polyadenylace; ženské pohlaví; Male; Genetic Predisposition to Disease; genetická predispozice k nemoci; Neoplasms; nádorové buněčné linie; nádory; Genome-Wide Association Study; Cell Line, Tumor; mužské pohlaví; Gene Expression Regulation, Neoplastic; lokus kvantitativního znaku